Ekologia w świecie dzieci. Na marginesie lektury Klimatycznych Olgi Ślepowrońskiej .......... 237 - Trześniewska-Nowak, Agnieszka (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
ECOLOGY IN THE WORLD OF CHILDREN. ON THE MARGINS OF READING CLIMATIC BY OLGA ŚLEPOWROŃSKAOlga Ślepowrońska’s book entitled Klimatyczni, published in 2020, is an interesting reading challenge for glottodidactics working with children and young people. Six protagonists tackle various ecological and social topics. It is a ready-made glottodidactic material, because within one story there is not only the text, but also a comic book and interesting although quite schematic illustrations. Klimatyczni by Olga Ślepowrońska is just one of the examples of contemporary children’s literature dealing with ecological issues. The publication is also in line with the current trend towards guide publications.